Rancang Bangun Alat Monitoring Stamina Atlet Basket Menggunakan Mikrokontroler Berbasis Internet Of Things - Rumata, Awaluddin Magain; Marlin, Syamsu; Harjono, Prawiro (FIKOM Universitas Bung Karno, 2023)
In this study discussed the importance of regulating stamina and heartbeat in basketball athletes, this device was designed to reduce the risk of fatalities in players to the end of death. To see the performance of the tool can be seen from some indicators about the stamina monitoring tool that can help to enhance the potential of players in preparing for the upcoming game, as well as can help the coach design the game strategy. The aim of this study is to look at the success of stamina monitoring devices designed for coaches, basketball athletes, and medical teams. The research methods used in this research are by collecting data through books and other literature, performing hardware design to explain schematic processes on tools as well as streams, and performing software design to describe schematical processes as tool commands. Based on the highest elevation data obtained to see the detected heart rate is at 60 and the lowest figure is at 44. It is expected that the subjects will be able to apply methods of exercise that can improve the stamina of basketball athletes.